Association of meeting 24-hour movement guidelines with low back pain among adults - Kaja Kastelic; Nejc Šarabon; Michael D. Burnard; Dean Lipovac; Željko Pedišić (AIMS Press, 2023)
Background: According to recently published 24-hour movement guidelines, adults should spend: ≥150 minutes/week in moderate-to-vigorous physical activity (MVPA); <8 hours/day in sedentary behaviour (SB); and 7-9 hours/day sleeping. Objective: We explored the association between meeting these recommendations and low back pain (LBP)-the most common musculoskeletal disorder. Methods: We collected self-reported data from 2333 adults about: MVPA, SB and sleep duration; frequency and intensity of LBP; and sociodemographic and lifestyle characteristics. Results: Meeting a combination of SB and sleep recommendations was associated with lower odds of LBP in the past week and past month (adjusted odds ratio [OR]: 0.64 and 0.52, respectively; p < 0.05 for both). Among LBP sufferers, meeting any combination of recommendations that includes sleep was associated with lower odds of frequent (OR range: 0.49-0.61; p < 0.05 for all) and intense (OR range: 0.39-0.66; p < 0.05 for all) LBP in the past week, while meeting a combination of SB and sleep recommendations or all three recommendations was associated with lower odds of intense LBP in the past month and past year (OR range: 0.50-0.68; p < 0.05 for all). The likelihood of experiencing higher frequency and intensity of LBP decreased with the number of recommendations met (p for linear trend < 0.05). Conclusion: Meeting the SB and sleep recommendations in combination is associated with a lower likelihood of LBP, while adhering to the overall 24-hour movement guidelines or any combination of recommendations that includes sleep is associated with lower frequency and intensity of LBP among LBP sufferers.